PELATIHAN PEMBUATAN SATE LILIT IKAN BANDENG SEBAGAI UPAYA MENINGKATKAN KETERAMPILAN DAN STATUS GIZI BAGI MASYARAKAT - Maulida, Alvina Fadila; Efrina, Efrina; Taruna, Shaka Ramadhan; Yuliarni, Ni Luh Putu (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Food is essential for human survival. The government has to provide and distribute food which is affordable and safe for the people to consume. The society in Muara Gembong District, Bekasi Regency, mainly makes a living from fish farming, agriculture, and trade. A vivid example of food availability is the utilization of local resources through 'food modification'. One popular culinary product is satay, which is usually made from meat. However, in this particular training, we used a local raw material, namely milkfish, as the main ingredient for making sate lilit (a type of satay). Milkfish contains high protein, namely around 20-24%; rich with micro and macro minerals; as well as has a soft, chewy, and savory texture. The results of the training, based on the results of the pre-test and post-test, showed an n-gain score of 0.6. This number signifies that the making of sate lilit was medium. Furthermore, in an effort to follow up on the aforementioned result, we hope that SMAN 1 Muara Gembong can become a part of the mentoring groups of the study program.